VET Again: Now as a VET Teacher - Duch, Henriette; Andreasen, Karen Egedal (International Journal for Research in Vocational Education and Training, 2017)
In 2010, a mandatory teacher training course was introduced for new vocational college teachers in Denmark. Since then, all vocational teachers have to complete the same course, regardless of practical work experience and educational background. After completion, they apply the knowledge to a very specific practice (i.e. teaching within a specific vocational field at a specific type of college). Thus, individual teachers experience different ‘learning trajectories’, depending on the vocational field and place of employment. They amass different experiences, including going back to school, just like newly enrolled students at a vocational college. This paper is based on empirical data from a qualitative study. It examines the learning trajectories of vocational teachers who choose to return to vocational colleges as VET teachers. Based on the analyses of two cases, we discuss the consequences for teachers’ pedagogical practice at vocational colleges and its potential for solving various challenges that colleges face.